Conceptual Understanding of Critical Factors That Drive Technopreneur Success in West Java - Leni Cahyani; Dandy Marcelino (Universitas Mercu Buana, 2022)
Objectives: Technology-based entrepreneurship is required in the globalization age. To accomplish this achievement, researchers must understand what factors might impact it. The purpose of this research is to identify what factors can drive the success of digital entrepreneurs (technopreneurs) in West Java. Methodology: This study use explanatory statistics, with Structural Equation Model analysis technique through SMART PLS 2.0. Sampling technique chosen was accidental sampling with 400 respondents. Finding: Partially and simultaneously, all factors have a positive and significant effect on business success. Therefore they have identified the following factor variables: entrepreneurial behavior, skills, educational background, and service quality. Conclusion: Technopreneurs in West Java are encouraged to continue to improve all factor variables as a capital for success. Considering that this research is only conducted on digital entrepreneurs in West Java, other researchers who want to conduct research with similar variables are advised to choose different objects with a wider scope for comparison.